STRATEGI PENGELOLAAN PARIWISATA KOTA SEMARANG MENUJU KOTA MICE (MEETING, INCENTIVE, CONFERENCE, EXHIBITION) SEBAGAI UPAYA MENINGKATKAN KUNJUNGAN WISATAWAN - Tri Setyaningsih Iswarsanty; Tri Yuniningsih (Journal of Public Policy and Management Review, 2017)
MICE is an activity aimed on accomplishing business interests. MICE industry has advantages such as: drawing a large number tourists, increasing period of stay and promoting tourism internationally. Since 2013, Semarang has been appointed as MICE city. To make Semarang as a MICE city, an optimal tourism management is needed. The focus and purpose of this research is to identify the tourism management strategy used by Ministry of Culture and Tourism in Semarang to achieve MICE. SWOT (Strength, Weakness, Opportunities, HMM) method analysis is performed in the strategic environment analysis of the area as an effort to improve tourism. This research uses qualitative descriptive type of study with data collection through interview, library study and document study. The research results conclude that the management of tourism in Semarang toward being a MICE city is not optimal. In its implementation, there is no normative document which states the city of Semarang as a MICE City that could be used as a reference to act. The quality and quantity of human resources are not sufficient. In addition, lack of promotion about the potentials of Semarang as a MICE city. By performing internal and external environment analysis, strategies can be obtained and then tested using a litmus test to measure whether the program is strategic or not based on an existing score. Based on these results, it is highly recommended for the Ministry of Tourism and Culture in Semarang to implement and apply the strategic programs that have been formulated consistently. This is done to optimize tourism management in Semarang towards achieving MICE in an effort to increase tourists or travelers.